O plano de desenvolvimento da escola (PDE escola) e a qualidade do ensino: da sua política de implementação, no governo FHC (1998- 2002), à sua configuração, no governo Lula (2003-2010) - SANTOS, Crisolita Gonçalves dos (Universidade Federal do Pará, 2020)
This article aims to contextualize how the School Development Plan (PDE Escola) has materialized in the governments of FHC (1998-2002) and Lula (2003-2010), since after ten years, the PDE Escola remains defending the improvement speech in the quality of Brazilian education. The text is an excerpt of the dissertation entitled “The management of educational policy in Igarapé-Miri and the PDE Escola: the place of autonomy and quality of education.” This is a qualitative study that used the field research for its enforcement. With the main focus on the discussion of PDE Escola and its focus on quality of teaching, the text defines the quality of education as a proposal which is beyond the measurable, surpassing the view that this improvement could be only related to quantifiable data.